Advances in information storage systems (World Scientific, 1998)
This volume covers friction-induced vibration, the influence of actuator-bearing grease composition, wear measurements for proximity recording heads, characteristics of a suspension assembly, design and analysis of the HDD Servo System, reluctance torque reduction, etc. It is organized into three parts: Mechanics and Tribology for Data Storage Systems; Dynamics and Controls for Data Storage Systems; and Electric Motors for Data Storage Systems.